2017
DOI: 10.3389/fmars.2017.00164
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Source Spectra of Ships from Long Term Recordings in the Baltic Sea

Abstract: Estimates of the noise source spectra of ships based on long term measurements in the Baltic sea are presented. The measurement data were obtained by a hydrophone deployed near a major shipping lane south of the island Öland. Data from over 2,000 close-by passages were recorded during a 3 month period from October to December 2014. For each passage, ship-to-hydrophone transmission loss (TL) spectra were computed by sound propagation modeling using 1. bathymetry data from the Baltic Sea Bathymetry Database (BSB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The transmission loss of the measured noise signature was modelled using XFEM code (Karasalo, 1994) to obtain the noise source at a reference distance. In their paper, Karasalo et al (2017) observed a good fit between the Wittekind predictions and the observed signals for cargo ships, tankers and tugboats, but larger differences were observed for passenger and RoRo vessels, with the Wittekind model overestimating the noise source levels. It is very likely that this is because the Wittekind model was mainly intended for large ocean-going vessels with a single fixed pitch propeller or a single controllable pitch propeller that are operated close to their design pitch (Dietrich Wittekind, personal communication, October 2017).…”
Section: Uncertainty Evaluationmentioning
confidence: 92%
See 1 more Smart Citation
“…The transmission loss of the measured noise signature was modelled using XFEM code (Karasalo, 1994) to obtain the noise source at a reference distance. In their paper, Karasalo et al (2017) observed a good fit between the Wittekind predictions and the observed signals for cargo ships, tankers and tugboats, but larger differences were observed for passenger and RoRo vessels, with the Wittekind model overestimating the noise source levels. It is very likely that this is because the Wittekind model was mainly intended for large ocean-going vessels with a single fixed pitch propeller or a single controllable pitch propeller that are operated close to their design pitch (Dietrich Wittekind, personal communication, October 2017).…”
Section: Uncertainty Evaluationmentioning
confidence: 92%
“…For examples of propagation modelling from multiple ships, which facilitates the evaluation of the sound pressure level at an arbitrary point in the water column, the reader is referred to e.g. Karasalo et al (2017) and Gaggero et al (2015). Presenting sound energy as a geographically distributed quantity will help to visualize noisy areas, as has also been investigated by Audoly et al (2015).…”
Section: Noise Source Map Generationmentioning
confidence: 99%
“…The transmission loss of the measured noise signature was modeled using XFEM code (Karasalo, 1994) to obtain the noise source at reference distance. In their paper, Karasalo et al (2017) observed a good fit between the Wittekind predictions and observed signals for cargo ships and tankers and tugboats, but larger differences were observed with passenger and RoRo vessels for which the Wittekind model overestimated the noise source levels. It is very likely that this is because the Wittekind model was mainly intended for large ocean-going vessels with a single fixed pitch propeller or a single controllable pitch propeller when they are operated close to their design pitch (Wittekind D, Oct 2017, personal communication).…”
Section: Uncertainty Evaluationmentioning
confidence: 90%
“…where Pk,m(t) is the sound power (in J s -1 ) emitted by ship m. This quantity is additive and facilitates the summation of ship specific noise energy over a specific time period (in Joules). The sound power map is more of a visual aid than a direct input dataset for noise propagation modeling, which may prefer point source description of noise sources (Karasalo et al, 2017).…”
Section: Noise Source Map Generationmentioning
confidence: 99%
“…This last is set at 87 dB(A) by the European Directive while if the second action level of 85 dB(A) is exceeded, the employer have to impose the use of hearing protection devices. The international community recognizes that noise from commercial ships may have both short and long-term negative consequences for both human (worker’s) life and marine life—especially marine mammals susceptible to underwater-radiated noise from ship’s sonars, propellers, and thrusters [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%